Chronic non-puerperal incomplete uterine inversion - Sofat, Agam; Dubey, Sunita; Tandon, Rimpy; Sehgal, Alka; Aggarwal, Purnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Chronic non-puerperal uterine inversion is an extremely rare diagnosis especially in younger women. The diagnosis commands high level of clinical suspicion supplemented with imaging. An emergency admission of a 35-year-old para 1 with submucosal fundal fibroid presenting with excessive menstrual flow with hemodynamic instability requiring multiple blood transfusions is presented. On abdominal examination slight suprapubic tenderness was made out with no palpable mass. Bimanual examination revealed a non-pediculated mass in upper vagina with a circular constriction around it. On ultrasound, cupping of fundus suggested uterine inversion. Pelvic MRI reaffirmed the findings of a highly vascularized intracavitary leiomyoma protruding through the cervix. After optimization patient underwent myomectomy and Haultain’s procedure followed by total abdominal hysterectomy with bilateral salpingectomy. Post-operative period was uneventful. Inversion is generally associated with fundal fibroid polyp but can rarely follow submucosal leiomyoma. Imaging helps preoperative planning of management.